Facial flushing response to alcohol and the risk of esophageal squamous cell carcinoma: A comprehensive systematic review and meta-analysis. (February 2016) - Andrici, Juliana; Hu, Sharon X.H.; Eslick, Guy D.
Highlights: Alcohol flushing response may increase the risk of developing esophageal cancer. We conducted a meta-analysis of studies to determine the link. The flushing response was associated with developing esophageal cancer. Moderate and heavy drinkers who experienced flushing were at a higher risk. Abstract: Objective: The alcohol flushing response is common among ethnic East Asian populations, and has been associated with an increased risk in developing esophageal cancer, especially squamous cell esophageal cancer (ESCC). We aimed to quantify the relationship between the facial flushing response to alcohol consumption and ESCC. Methods: We conducted a meta-analysis of studies reporting on the association between the facial flushing response to alcohol consumption and ESCC. Pooled odds ratios (OR) and 95% confidence intervals (CI) were calculated using a random effects model for the risk of ESCC associated with the facial flushing response in general, as well for different levels of alcohol consumption. Four databases, Medline, PubMed, Embase, and Current Contents Connect, were searched to 31August 2015. Results: Seven studies, with 1014 ESCC cases, met the inclusion criteria. There was a positive relationship between the flushing response and ESCC (OR 1.97; 95% CI 1.25–3.13). Heterogeneity was observed ( I 2  =  80%, P  < 0.001). Publication bias was not present. An increased risk of ESCC was present in the moderate and heavy drinkers who experienced flushing, compared with moderate and heavy drinkers who did not (OR 2.54; 95% CI 1.64–3.91, and OR 2.90; 95% CI 1.82–4.82, respectively). Conclusion: Individuals who experience a facial flushing response to alcohol intake may be at increased risk of developing ESCC, particularly if they are moderate to heavy drinkers.